PENGENALAN KETERAMPILAN MENTAL KEPADA ATLET KOTA MAKASSAR - Muflih Wahid Hamid; Nukhrawi Nawir; Faradillah Firdaus; Muhammad Rhesa; Arfandi Akkase (Universitas Negeri Makassar, 2023)
This activity aims to introduce and sharpen the knowledge of KONI Makassar athletes on mental skills that will play a very important role in the training and matches they will take part in. This activity departs from a needs analysis which is carried out using observation and interview methods to find out what things athletes need to improve in terms of psychological skills, it turns out that many athletes do not know in detail the mental skills needed to become successful athletes. The basic theory that is used as a reference in making psychoeducational materials is Jack Lesyck's nine mental skills for successful athletes. This theory is used because it is considered very holistic and comprehensive to help athletes have the mental skills that must exist in them to become successful athletes. Based on the results of the pre and post-test, it was concluded that the psychoeducation arranged by the research team provided knowledge and sharpened information about the mental skills possessed by athletes in Makassar City. Further research is expected that athletes will be given special assistance so that more mental exercises can be carried out by athletes